Which Histometric Analysis Approach Is More Reliable for Assessing Histological Bone Tissue Samples? - Pereira, Rodrigo dos Santos (2022)
This study aims to evaluate the grid of Merz and ImageJ methods for histometric quantification, verifying which is more reliable and defining which is most suitable based on the time required to perform. Thirty histological samples of maxillary sinuses grafted with xenografts were evaluated using an optical light microscope attached to an image capture camera and connected to a microcomputer. The images were digitalized and recorded as a TIFF image, and the new bone formation was evaluated using the grid of Merz and ImageJ. The Bland–Altman analysis was used to identify the agreement between the methods and determine suitable future research options. The timing of the quantification was also performed to identify a possible advantage. The mean value for the quantification analysis timing for the grid of Merz was 194.9 ± 72.0 s and for ImageJ was 871.7 ± 264.4, with statistical significance between the groups (p = 0.0001). The Bland–Altman analysis demonstrated a concordance between the methods, due to the bias being next to the maximum concordance (−1.25) in addition to the graphic showing the scattering points next to the mean of differences and inside of limits of agreement. Thus, it was demonstrated that the grid of Merz presents reliable outcomes and advantages over the ImageJ methodology regarding the time spent to contour the areas of interest.